Life in the fast lane: drugs, hedonistic lifestyles, and economic crime - Felson, Richard B. (Crime & delinquency, 2019)
We examine whether economic crimes are committed to fund drug addiction and/or to fund a hedonistic lifestyle. To address motivation, we estimate reciprocal relationships between economic crime and drug use and between economic crime and hedonistic activity generally. Analyses are based on event calendar data collected from 715 male offenders. Both simultaneous (within-month) relationships and effects involving a 1-month lag are examined. Offenders were more likely to engage in property crime and drug dealing during months in which they used hard drugs, marijuana, and alcohol, and when they engaged in more frequent unstructured socializing. The results from lagged models suggested that hedonistic activities lead to economic crime and economic crime creates opportunities for more frequent hedonistic activity.